Uses of social media Facebook & Twitter by Ecuadorian radio: Management in most important social network in Ecuadorian radios in a convergence time[Gestión de las Emisoras de Radio Nacionales de Ecuador en Facebook y Twitter: Uso de las principales Redes Sociales del medio radial en Ecuador en tiempos de convergencia] - Martinez Vazquez, J. (2015)
Radio currently is in the middle of a change process, released by new technologies in communication. These new digital spaces supply new relationship with audience and new ways of participation. This research analyses how Ecuadorian radio channels uses new technologies and social Networks in the most important social network.